Fluid overload and mortality in critically ill patients with severe heart failure and cardiogenic shock–An observational cohort study - Waskowski, Jan; Michel, Matthias C.; Steffen, Richard; Messmer, Anna S.; Pfortmueller, Carmen A. (Frontiers in Medicine, 2022)
Objective Patients with heart failure (HF) and cardiogenic shock are especially prone to the negative effects of fluid overload (FO); however, fluid resuscitation in respective patients is sometimes necessary resulting in FO. We aimed to study the association of FO at ICU discharge with 30-day mortality in patients admitted to the ICU due to severe heart failure and/or cardiogenic shock. Methods Retrospective, single-center cohort study. Patients with admission diagnoses of severe HF and/or cardiogenic shock were eligible. The following exclusion criteria were applied: (I) patients younger than 16 years, (II) patients admitted to our intermediate care unit, and (III) patients with incomplete data to determine FO at ICU discharge. We used a cumulative weight-adjusted definition of fluid balance and defined more than 5% as FO. The data were analyzed by univariate and adjusted univariate logistic regression. Results We included 2,158 patients in our analysis. 185 patients (8.6%) were fluid overloaded at ICU discharge. The mean FO in the FO group was 7.2% [interquartile range (IQR) 5.8–10%]. In patients with FO at ICU discharge, 30-day mortality was 22.7% compared to 11.7% in non-FO patients (p < 0.001). In adjusted univariate logistic regression, we did not observe any association of FO at discharge with 30-day mortality [odds ratio (OR) 1.48; 95% confidence interval (CI) 0.81–2.71, p = 0.2]. No association between FO and 30-day mortality was found in the subgroups with HF only or cardiogenic shock (all p > 0.05). Baseline lactate (adjusted OR 1.27; 95% CI 1.13–1.42; p < 0.001) and cardiac surgery at admission (adjusted OR 1.94; 95% CI 1.0–3.76; p = 0.05) were the main associated factors with FO at ICU discharge. Conclusion In patients admitted to the ICU due to severe HF and/or cardiogenic shock, FO at ICU discharge seems not to be associated with 30-day mortality.